Effects of asymmetrical postural demands on sternocleidomastoid reflex in the startReact paradigm - Adjei, Ermyntrude N. A.; Wright, Kelsey; Dewald, Julius P. A.; Yao, Jun (Frontiers in Human Neuroscience, 2025)
IntroductionstartReact, the rapid release of a planned movement following a startling acoustic stimulus (usually >100 dB), is widely used to assess reticulospinal tract (RST) involvement in motor control. The sternocleidomastoid (SCM) reflex within 120 ms often identifies true startle responses, i.e., responses facilitated by RSTs in the absence of cortical control. However, as the SCM is a postural muscle, its reflexive activation may be influenced by inhibitory anticipatory postural adjustments (APAs), particularly during tasks with greater head/neck postural demands.MethodsWe compared SCM activation during unilateral shoulder abduction (SABD) versus hand opening (OPEN) tasks. Due to the increased asymmetrical head/neck postural demands in SABD, we hypothesized an APA-induced delay in SCM activation during SABD compared to the OPEN task, with a contralateral bias due to contralateral cortical circuits triggering APAs.ResultsOur results revealed significantly longer SCM latency—exceeding the 120 ms cutoff—during SABD relative to OPEN. This suggested that APAs during postural tasks, resulting from unilateral SABD, altered the expression of the startReact response. To confirm this finding, we implemented an innovative, data-driven method to determine the appropriate SCM cutoff based on the physiological difference between startle-induced SCM reflexes and task-induced SCM activation. Using this method, we observed reduced contralateral SCM reflexive activation compared to ipsilateral, during SABD but not in OPEN.DiscussionThis provides evidence for the first time that SCM reflexive activation in startReact is posture-dependent. Our novel classification method offers a robust framework for identifying true startle responses across different tasks, offering broader applicability for studies investigating RST involvement in motor control.